Genetic Fingerprinting of Bacillus thuringiensis Isolates by Randomly Amplified Polymorphic DNA Polymerase Chain Reaction (RAPD-PCR) - Sahukhal, Gyan Sundar; Shrestha, Upendra Thapa; Lekhak, Binod (Nepal Journal of Science and Technology, 2010)
Random Amplified Polymorphic DNA (RAPD) is a method of producing a genetic fingerprint of a particular species without its prior genetic information. Relationship between species may be determined by comparing their unique fingerprint information. B. thuringiensis was isolated from soil samples of Khumbu base camp of Everest region, Nepal. Crystal protein (delta endotoxin) producing strains (46 from Phereche and 40 from Sagarmatha national park) were tested against a series of 100 decamer RAPD primers (codes 201-300, obtained from University of British Columbia) by RAPD PCR. Primer 284 was found the best among the tested primers and the reaction condition for PCR was optimized with a PCR buffer containing 10mM Tris HCl, 50 mM KCl, 3 mM MgCl2 with pH 8.3.; 200ìm dNTPs each, 1U Taq polymerase , 40 pmol decamer primers, 20 ng template DNA and 1% DMSO as a final concentrations in 25ìl reaction mixture. The thermal programme was programmed as initial denaturation temperature at 94°C for 5 min followed by 35 cycles with denaturation at 94°C for 1 min, annealing at 36°C for 1 min and extension at 72°C for 2 mins with final extension temperature at 72°C for 10 min. Higher polymorphic fragments were found in the range between 700-900 bp. Next to it, the range of 400-700 and 1200-1600 bp were, too, highly polymorphic among the isolates. The discriminatory capacity (D) of the RAPD-PCR was found to be 0.9901. The isolates of cold tolerant B. thuringiensis from high altitude regions were found rich in genomic polymorphism. Nepal Journal of Science and Technology Volume 10, 2009 December Page: 97-103